Graphene and graphene-based nanostructures - Krive, I.V.; Loktev, V.M.; Shekhter, R.I. (Физика низких температур, 2008)
This issue of the journal «Fizika Nizkikh Temperatur»
is dedicated to the discovery of graphene — a monolayer
graphite — in 2004.